2012
DOI: 10.1089/fpd.2011.0942
|View full text |Cite
|
Sign up to set email alerts
|

rROP2186–533: A Novel Peptide Antigen for Detection of IgM Antibodies AgainstToxoplasma gondii

Abstract: Toxoplasma gondii infections are prevalent in a wide range of mammalian hosts including humans. Infection in pregnant women may cause the transmission of parasite to the fetus that makes serious problems. IgM antibodies against Toxoplasma (Toxo-IgM) have been believed to be significant indicators for both recently acquired and congenital toxoplasmosis. So far, however, there has not been any recognized protein of T. gondii that specifically reacts to IgM antibodies. Here, an antigen exclusively for detection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 13 publications
2
10
0
1
Order By: Relevance
“…In the present study, the ELISA-rROP2 reacted with the same specificity to samples from acute infection and samples from chronic infection. However, similar to Liu et al (2012) , we detected a higher sensitivity and NPV in the samples known to contain anti- T. gondii IgM in the groups with probable acute infection (B) and possible acute infection (C) than in the other groups (A and I).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the present study, the ELISA-rROP2 reacted with the same specificity to samples from acute infection and samples from chronic infection. However, similar to Liu et al (2012) , we detected a higher sensitivity and NPV in the samples known to contain anti- T. gondii IgM in the groups with probable acute infection (B) and possible acute infection (C) than in the other groups (A and I).…”
Section: Discussionsupporting
confidence: 85%
“…Other rROPs have been evaluated, such as rROP8, which had a specificity of 94% and sensitivity of 90% for early acute toxoplasmosis and sensitivities of 92% and 82% for acute and chronic toxoplasmosis, respectively ( Sonaimuthu et al 2014 ). Liu et al (2012) demonstrated that 100% of the serum samples that contained anti- T. gondii IgM, but not IgG showed positive IgM. However, none of them showed positive IgG when rROP2 was used as an antigen in pregnant women.…”
Section: Discussionmentioning
confidence: 97%
“…Beghetto et al (2006) reported that recombinant antigens could provide the basis for standardized commercial tests for the serodiagnosis of toxoplasmosis. Other recombinant proteins had been used for serodiagnosis, such as SAG1 (Chahed Bel-Ochi et al, 2013), ROP2 (Liu et al, 2012), MIC1 (Holec et al, 2008), and GRA7 (Wang et al, 2014). Antibodies against T. gondii produced in chronic and acute infection could be recognized by MAG1 protein, but it is mostly associated with chronic toxoplasmosis since MAG1 is abundantly expressed within the cyst and in the cyst wall surrounding the bradyzoites (Ferguson and Parmley, 2002); thus there may be false-negative results when applied by MAG1-based serology methods from acute toxoplasmosis samples since lower anti-MAG1 antibodies would be produced in this stage.…”
Section: Discussionmentioning
confidence: 99%
“…In many of these studies, it was evaluated the diagnostic performance of chimeric antigens, recombinant proteins or peptides derived from T. gondii proteins [8][9][10]. Among the antigenic options currently available, an elegant approach is the use of synthetic peptides produced from the amino acid sequences of B cell epitopes predicted by in silico analysis of T. gondii antigens.…”
Section: Discussionmentioning
confidence: 99%
“…The use of synthetic peptides in serological tests has some advantages, such as the precise knowledge of the antigen composition, which is contamination-free, the standardization of methods and the lower costs of the procedures, when compared to those ones using total antigens. Besides, the properly selection of epitopes from antigens differentially expressed by the parasite during the acute or chronic phases could contribute to differentiate phases of infection [8,10].…”
Section: Discussionmentioning
confidence: 99%